Effects of polycyclic aromatic compounds in fine particulate matter generated from household coal combustion on response to EGFR mutations in vitro. (November 2016) - Ho, Kin-Fai; Chang, Chih-Cheng; Tian, Linwei; Chan, Chi-Sing; Musa Bandowe, Benjamin A.; Lui, Ka-Hei; Lee, Kang-Yun; Chuang, Kai-Jen; Liu, Chien-Ying; Ning, Zhi; Chuang, Hsiao-Chi
Abstract: Induction of PM2.5 -associated lung cancer in response to EGFR -tyrosine kinase inhibitors ( EGFR -TKI) remains unclear. Polycyclic aromatic hydrocarbons (PAHs) and their polar derivatives (oxygenated PAHs: OPAHs and azaarenes: AZAs) were characterized in fine particulates (PM2.5 ) emitted from indoor coal combustion. Samples were collected in Xuanwei (Yunnan Province), a region in China with a high rate of lung cancer. Human lung adenocarcinoma cells A549 (with wild-type EGFR ) and HCC827 (with EGFR mutation) were exposed to the PM2.5, followed by treatment with EGFR -TKI. Two samples showed significant and dose-dependent reduction in the cell viability in A549. EGFR -TKI further demonstrated significantly decreased in cell viability in A549 after exposure to the coal emissions. Chrysene and triphenylene, dibenzo[ a, h ]anthracene, benzo[ ghi ]perylene, azaarenes and oxygenated polycyclic aromatic hydrocarbons (carbonyl-OPAHs) were all associated with EGFR -TKI–dependent reduced cell viability after 72-h exposure to the PM2.5 . The findings suggest the coal emissions could influence the response of EGFR -TKI in lung cancer cells in Xuanwei. Graphical abstract: Highlights: Associations between Mutations in EGFR and coal-emitted PM2.5 were determined. Cell viability in A549 exposed to the coal PM2.5 samples significantly decreased. PACs were associated with reduction of cell viability by EGFR -TKI. Coal-emitted PM2.5 may influence the response of EGFR -TKI in lung cancer cells. Abstract : The PM2.5 emitted from coal combustion shows association with EGFR -TKI response in vitro . This association can be further linked with chrysene and triphenylene, dibenzo[ a, h ]anthracene, benzo[ ghi ]perylene, azaarenes and oxygenated PAHs.